Aktywność angiogenna i stężenie VEGF w surowicach chorych na cukrzycę powikłaną retinopatią prostą - Skopiński, Piotr; Duda-Król, Barbara; Lipińska, Anna; Sommer, Ewa; Chorostowska-Wynimko, Joanna; Demkow, Urszula; Szaflik, Jerzy; Skopińska-Różewska, Ewa; Struzik, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Diabetic retinopathy is one of the most common causes of blindness. The majority of studies concerning this problem were performed in patients with late stage of disease, demonstrating proliferative retinopathy, when malformations of retinal vessels became irreversible (1). Numerous angiogenic factors related to retinal angiogenesis have been described. Among them, VEGF is thought to be the major mediator of proliferative retinopathy (2,3,4). Our present study was performed on sera collected from patients with earlier stage of ocular complications, manifested as background retinopathy. We have believed that the knowledge of the earliest events leading to pathological angiogenesis may be valuable for establishing some prophylactic regimens. Sera of 22 persons with DM1, aged 33-70 years, 37 persons with DM2, aged 37-79 years, 51 healthy people, aged 22-80 years (as controls) were studied. Direct serum-induced cutaneous angiogenesis test in mice (SIA) was applied (5,6). VEGF concentration in sera was mesured by ELISA (R & D Systems) test. Angiogenic activity and VEGF concentration of DM1 patients sera were highly statistically lower than these parameters in DM2 patients and controls.